Awareness among women in Malaysia on the issue of financial abuse - Norjannah Abu Bakar,; Nurul Aliyah Sham Rambely,; Ayu Indayu Mohd Zohdi,; Mohd Yasir Yamin Mohd Razali,; Elshafi Hamdan Hamed Mohammed,; Wu, Yihui; Suzana Muhamad Said, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Financial abuse refers to over control of a person’s money, income or asset. The problem occurs when lack of awareness about financial abuse and victims did not realize that they are experiencing it. This paper explores the issue of financial abuse among women in Malaysia and the objective is to analyze and understand the awareness of financial abuse among women in Malaysia. 231 women respondents had agreed to join a survey and data was collected through the distribution of online questionnaires using Google Forms and the data was analyzed using Google Form’s results. The result of the study shows that 40.3% of respondents understood financial abuse, while 35.9% of respondents agreed that financial abuse was incurred from individuals they knew. The study also found that 1.7% of respondents faced the issue of being forced to use their money without consent and hand over their money to certain parties. Strengthening the laws related to finance management and inheritance may protect women. Financial institutions also are expected to be the first to detect if this issue happens. The best way to overcome financial abuse against women is to seek knowledge and education. It should be considered a crime and awareness are extremely important.